Essential oil from hibiscus flowers through advanced microwave-assisted hydrodistillation and conventional hydrodistillation - Rassem, Hesham H. A.; Nour, Abdurahman Hamid; Ali, Gomaa A. M.; Masood, Najat; Al-Bagawi, Amal H.; Alanazi, Tahani Y. A.; Magam, Sami; Assiri, Mohammed A. (Hindawi Publishing Corporation, 2022)
Due to the increased demand and importance of essential oils in medicinal applications, advanced essential oil extraction techniques have been employed. Both conventional hydrodistillation (HD) and microwave-assisted hydrodistillation (MAHD) were employed to extract the essential oils from the hibiscus flower. Extraction time and solvent polarity were the most critical factors. Scanning electron microscopy (SEM) was used to investigate the surface morphologies of raw powdered hibiscus flowers (not exposed to any pretreatment) and pretreated powdered hibiscus flowers (exposed to methanol absorption for 60 minutes prior to extraction). Extractive chemistry analysis utilizing Fourier transform infrared (FTIR) spectroscopy was performed on the volatile oil obtained by MAHD. Different peaks in the gas chromatography/mass spectrometry (GC/MS) analysis indicated the presence of thirty-seven different compositions. MAHD was more energy efficient, had higher yield production, and was environmentally friendly, reducing HD's overall carbon footprint by 40%. Oxygenated monoterpene, sesquiterpene, and sesquiterpene hydrocarbons were found in the hibiscus flower's crude extract. Moreover, the methanolic extract of Hibiscus rosa-sinensis has potent antioxidant properties. A hibiscus flower extract had scavenging activities of 51.2% at 0.2 mg/mL, 0.3% at 0.6 mg/mL, 0.8% at 1.0 mg/mL, and 68.5% at 1.2 mg/mL against DPPH free radicals. Therefore, the MAHD method is well-suited to extracting essential oils from hibiscus flowers, and the resulting oil has the potential to provide significant therapeutic advantages.